2015
DOI: 10.1134/s2070205115020021
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study of the behavior of copper inhibition in 1 M HNO3 by Euphorbia Helioscopia linn. extract as green inhibitor

Abstract: The inhibitive effect of the Euphorbia Helioscopia linn. extract (EHE) on the corrosion of copper in 1 M HNO 3 has been evaluated by means of potentiodynamic polarization, electrochemical impedance spectroscopy (EIS) and electrochemical frequency modulation (EFM) techniques. The calculated adsorp tion thermodynamic parameters indicated that the adsorption was a spontaneous, exothermic process accompanied by an increase in entropy. The inhibition efficiency increases with increasing the concentration of the inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The Nyquist diagrams were examined to be single capacitive loops suited with a one-time constant (i.e., that seemed to be a single capacitive loop). 56 The capacitive loop at the high- frequency area is assigned to the corrosion product/inhibitor lm, and the capacitive loop at the middle-frequency area is assigned to the charge transfer reaction at the electrode/ solution interface. 57 The size of the capacitive loop was found to rise with concentrations of the H 2 HEH and H 2 MEH.…”
Section: Eis Measurementsmentioning
confidence: 99%
“…The Nyquist diagrams were examined to be single capacitive loops suited with a one-time constant (i.e., that seemed to be a single capacitive loop). 56 The capacitive loop at the high- frequency area is assigned to the corrosion product/inhibitor lm, and the capacitive loop at the middle-frequency area is assigned to the charge transfer reaction at the electrode/ solution interface. 57 The size of the capacitive loop was found to rise with concentrations of the H 2 HEH and H 2 MEH.…”
Section: Eis Measurementsmentioning
confidence: 99%
“…The apparent energy of activation (Ea*), activation enthalpy (∆H*), and activation entropy (∆S*) for steel corrosion in 1 M HCl solution were calculated using the Arrhenius form equation in the absence and presence of various concentrations of L-proline [14] : (2) and transition state equation [15] :…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Adsorption mechanism of inhibitors at copper/emulsion interface are usually investigated by Langmuir, Frumkin and Temkin isotherms according to the equations (Qiang et al, 2017;Abdallah and Shalabi, 2015):…”
Section: Adsorption Isotherm Studiesmentioning
confidence: 99%
“…It was found that the most suitable model to fit the experimental results obeys the Langmuir isotherm (Figure 4), with all linear regression coefficients (R 2 ) approaching 1. It reveals that the adsorption process of all inhibitors on copper immersed in emulsions follows Langmuir isotherm (Abdallah and Shalabi, 2015), the intercept of the straight lines between C and C/u is 1/K (Li et al, 2014). The free adsorption energy (DG 0 ads ) can be obtained by the following formula (Huo et al, 2013):…”
Section: Adsorption Isotherm Studiesmentioning
confidence: 99%